Livro de poesia no Ensino Médio : possibilidade de interação - Dalenogare, Rosana Andres (My University, 2018)
This research aims to verify the possibilities of interaction between poetry and the probable receivers - students enrolled in High School - from the study of the anthology Poesia faz pensar, that belongs to the collection of the Programa Nacional Biblioteca da Escola – Ensino Médio (PNBE 2013). The research conceives the education as a continuous process, that occurs through the relations between the being and the world and assists in the humanization of the subject (FREIRE, 1987) and Literature as a human right, which can contribute to the autonomy, by allowing the reader to reflect on his condition from the possibility of accessing and living other realities through literary reading (CANDIDO, 2011). The methodology, bibliographical and analytical research, analyzes paratexts (GENETTE, 2009) from the selected book and six poems of the anthology, respecting predominantly the literary periods, authors and themes of the poems. The investigation establishes the poetry potentialities for the human formation of the reader. The research seeks to highlight the potentialities of poetry for a human formation of the reader and, as results, we perceive that each poetry has singular characteristics, in the structure, in the way of approaching the exposed , or in the historicity that, when studied together with others aspects, can contribute to the formation of subjects that know about their cultures and that think autonomously, guided by their experiences and critical sensors. At the conclusion of the dissertation, the reflections generated by the analysis indicate the selection of poetry from de book contemplate a variety of themes that allow a reflection on different concepts of daily life and that this reflection can be mediated by paratextual elements associated with the teacher 's presence. Thus, the reader of the High School can have in the anthology, a support in his human formation
Esta investigação objetiva analisar possibilidades de interação entre a poesia e os prováveis destinatários - estudantes matriculados no Ensino Médio -, a partir do estudo da antologia Poesia faz pensar, pertencente ao acervo do Programa Nacional Biblioteca na Escola – Ensino Médio (PNBE 2013). A pesquisa concebe a educação como processo contínuo, que ocorre por meio das relações entre o ser e o mundo e que auxilia na humanização do indivíduo (FREIRE, 1987) e a Literatura como direito humano, que pode contribuir para a autonomia, ao propiciar a reflexão do leitor sobre sua condição a partir da possibilidade de acessar e viver outras realidades por meio da leitura literária (CANDIDO, 2011). A metodologia empregada, pesquisa bibliográfica e analítica, analisa paratextos (GENETTE, 2009) da obra selecionada e seis poesias integrantes da antologia, respeitando, predominantemente, os períodos literários, autores e temas dos poemas. A investigação busca destacar as potencialidades da poesia para a formação humana do leitor e, como resultados, percebemos que cada poesia possui características singulares, seja na estrutura, no modo de abordar a temática eleita, ou na historicidade que ao ser estudada, ao lado de outros aspectos, pode contribuir na formação de sujeitos conhecedores de suas culturas e que pensem de forma autônoma, guiados por suas experiências e senso crítico. Ao concluir a dissertação, as reflexões geradas pela análise indicam que a seleção de poesias da obra contempla variedade de temas que propiciam a reflexão sobre diversos assuntos do cotidiano e que essa reflexão pode ser mediada pelos elementos paratextuais presentes no exemplar associados a presença do professor. Em síntese, o leitor do Ensino Médio pode ter na antologia de poesia um auxílio em sua formação humana.
Keywords: Leitura - Estudo e ensino; Poesia; Ensino médio; Reading - Study and teaching; Poetry; High school